1997
DOI: 10.1002/(sici)1096-9845(199701)26:1<5::aid-eqe619>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Transfer Functions for Rigid Rectangular Foundations

Abstract: SUMMARYClosed-form expressions and comprehensive numerical solutions are presented for the transfer functions of surfacesupported, rigid, rectangular foundations excited by horizontally polarized, incoherent shear waves for which the motions are parallel to one of the foundation sides. The free-field ground motion is specified stochastically in terms of a local power spectral density function and an orthotropic incoherence function which decays exponentially with the square of the excitation frequency and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 0 publications
0
36
0
Order By: Relevance
“…Analytical solutions for base-slab averaging in various incident waves have been developed for circular and rectangular foundations (Scanlan 1976;Newmark et al 1977;Luco and Wong 1986;Luco and Mita 1987;Veletsos and Prasad 1989;Veletsos et al 1997;Kim and Stewart 2003). Figure 1a shows the transfer function proposed by Veletsos et al (1997) for vertically incident incoherent waves, where a and b are the full footprint dimension of rectangular foundations, andã 0 is a dimensionless frequency parameter. In FEMA-440 document,ã 0 is approximate estimation as follows for rectangular foundations.…”
Section: Foundation Input Motionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Analytical solutions for base-slab averaging in various incident waves have been developed for circular and rectangular foundations (Scanlan 1976;Newmark et al 1977;Luco and Wong 1986;Luco and Mita 1987;Veletsos and Prasad 1989;Veletsos et al 1997;Kim and Stewart 2003). Figure 1a shows the transfer function proposed by Veletsos et al (1997) for vertically incident incoherent waves, where a and b are the full footprint dimension of rectangular foundations, andã 0 is a dimensionless frequency parameter. In FEMA-440 document,ã 0 is approximate estimation as follows for rectangular foundations.…”
Section: Foundation Input Motionsmentioning
confidence: 99%
“…It has been shown that doing a running average to the free-field motion in time domain is exactly equal to using the following low pass filter in frequency domain (Holloway 1958;Hudson 1979). |H(f)| ap.,Tw=0.04s ap.,Tw=0.08s ap.,Tw=0.12s ex., be=20m ex., be=43m ex., be=72m Veletsos et al (1997) for vertically incident incoherent waves; (b) Comparison between approximate transfer functions (ap.) and the transfer functions (ex.)…”
Section: Foundation Input Motionsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that the dynamic behavior of buildings can be affected by the presence of a deformable soil-foundation system, which possibly makes the seismic response of a flexibly-supported structure different from that of the rigidly-supported counterpart [1] by: (i) lengthening the fundamental period of the structure; (ii) allowing additional dissipation of energy into the soil by radiation and hysteresis; (iii) filtering the signal transmitted to the structure by incident waves, as a result of both base slab averaging [2] and embedment effects [3].…”
Section: Introductionmentioning
confidence: 99%